Analysis Of Audience Reception To Youtube Content One Percent-Indonesian Life School (In The Video Susah Ngobrol Karena Pemalu? Cara Mengatasi Kecemasan Sosial) - Meytriantara, Rizky; Farida Nurfalah (CV. AFDIFAL MAJU BERKAH, 2024)
Social media serves as a communication tool tailored to users' needs and as a platform for disseminating health education messages to internet users. Satu Persen – Indonesian Life School utilizes its YouTube account to convey messages focusing on education and lessons not taught in schools. In this study, Stuart Hall's theory is employed to analyze how audiences respond to the educational messages from Satu Persen – Indonesian Life School in the contexts of dominant hegemonic position, negotiated position, and oppositional position. The research findings indicate that the audience consuming content from the Satu Persen – Indonesian Life School YouTube account in the video